2018
DOI: 10.3390/molecules24010019
|View full text |Cite
|
Sign up to set email alerts
|

Fungi-Mediated Biotransformation of the Isomeric Forms of the Apocarotenoids Ionone, Damascone and Theaspirane

Abstract: In this work, we describe a study on the biotransformation of seven natural occurring apocarotenoids by means of eleven selected fungal species. The substrates, namely ionone (α-, β- and γ-isomers), 3,4-dehydroionone, damascone (α- and β-isomers) and theaspirane are relevant flavour and fragrances components. We found that most of the investigated biotransformation reactions afforded oxidized products such as hydroxy- keto- or epoxy-derivatives. On the contrary, the reduction of the keto groups or the reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…The biocatalytic activity of Aspergillus niger was investigated because it has been demonstrated that this microorganism can degrade coumarin and dihydrocoumarin as well as substituted coumarins [10,11,14]. Similarly, we singled out Geotrichum candidum, Penicillium adametzii and Penicillium corylophilum since these species are able to reduce the conjugated double bond of different α,β-unsaturated ketones and lactones [25,38,39]. Finally, we selected two specific strains of Penicillium camemberti and Penicillium roqueforti, which are currently used in the dairy industry.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The biocatalytic activity of Aspergillus niger was investigated because it has been demonstrated that this microorganism can degrade coumarin and dihydrocoumarin as well as substituted coumarins [10,11,14]. Similarly, we singled out Geotrichum candidum, Penicillium adametzii and Penicillium corylophilum since these species are able to reduce the conjugated double bond of different α,β-unsaturated ketones and lactones [25,38,39]. Finally, we selected two specific strains of Penicillium camemberti and Penicillium roqueforti, which are currently used in the dairy industry.…”
Section: Resultsmentioning
confidence: 99%
“…Herein, we describe the results obtained by our work that, besides confirming and extending those described by previous researches, suggested the prospective utility of the yeasts Torulaspora delbrueckii, Kluyveromyces marxianus and of the fungus Penicillium camemberti for natural dihydrocoumarin production. As we recently set up a research program aimed at the biotechnological production of natural flavours [20][21][22][23][24][25][26], we decided to design a new process for the preparation of natural dihydrocoumarin based on the microbial reduction of coumarin. To this end, we undertook a comprehensive study intended to select microbial strains showing good tolerance to relatively high coumarin concentrations and that could efficiently perform the reduction of its conjugated double bond.…”
Section: Introductionmentioning
confidence: 99%
“…Again, similar products were obtained in fungi-mediated biotransformation of αdamascone but with lower conversion rates, maybe due to the toxicity of these compounds to fungal cultures. 3 Interestingly, in addition to ring oxygenation, AaeUPO, MroUPO, and rCciUPO oxygenated the terminal position of the side chain (Figure 3) being the predominant reaction (80% of the total products) for the former UPO (Table 4 and Figure S5). In these reactions, the formation of the terminal alcohol (10-hydroxy-α-damascone, 10-OH-α-D) was followed by its over-oxygenation, producing the corresponding aldehyde (4oxo-4-(2,6,6-trimethylcyclohex-2-en-1-yl)but-2-enal, 10-CHOα-D) and the carboxylic acid (4-oxo-4-(2,6,6-trimethylcyclo-hex-2-en-1-yl)but-2-enoic acid, 10-COOH-α-D).…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…2 The introduction of hydroxyl or keto functionalities in these compounds reduces their volatility and increases the longlasting odor. 3 Most of these derivatives (3-hydroxy and 3-oxoα-ionone, 4-hydroxy-and 4-oxo-β-ionone, and hydroxy-βdamascone isomers) are present in plants but in very small amounts and extraction is not a viable process for their industrial use. For this reason, they are usually prepared by chemical synthesis and, therefore, alternative methods for the bioproduction of these compounds are of high industrial interest.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Other studies have focused on the catalytic transformation of carotenoids and monoterpenes such as α- and β-pinene and β-carotenes to produce precursor compounds [ 13 , 14 , 15 ]. Recently, fungi belonging to the phyla Ascomycota, Zygomycota, and Basidiomycota were shown to biotransform several apocarotenoid flavour agents and fragrance components [ 1 , 2 , 16 ]. Studies on various types of microorganisms—namely, prokaryotes and eukaryotes—highlighted the ability of basidiomycete fungi to transform the aforementioned compounds [ 17 ], as these fungi either produced enzymes that actively oxidised monoterpenes and carotenes [ 18 , 19 , 20 ] or possessed metabolic pathways for the synthesis of volatile aromatic compounds [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%